2014
DOI: 10.1007/s40474-014-0022-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Behavioral Profiles of Children with Fetal Alcohol Spectrum Disorders

Abstract: The last two decades have witnessed a rapid growth of published data on the cognitive and behavioral functioning of children with fetal alcohol spectrum disorders (FASD). The main of aim of this paper is to review cognitive and behavioral data on FASD using a causal modeling framework originally proposed by Morton and Frith [1,2], according to which data pertinent to a neurodevelopmental disorder can be organized at three levels: neurobiology, cognition, and behavior. In this review, we confine ourselves to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 129 publications
4
37
0
Order By: Relevance
“…Several studies have highlighted the deficits in executive functioning associated with PAE [2529]. Direct neuropsychological assessment indicates the greatest deficits in cognitive flexibility/set-shifting, abstraction, spatial working memory, and verbal fluency [30] and parent reports indicate greatest impairment in inhibitory control and problemsolving [31].…”
Section: Neurocognitive Impairmentmentioning
confidence: 99%
“…Several studies have highlighted the deficits in executive functioning associated with PAE [2529]. Direct neuropsychological assessment indicates the greatest deficits in cognitive flexibility/set-shifting, abstraction, spatial working memory, and verbal fluency [30] and parent reports indicate greatest impairment in inhibitory control and problemsolving [31].…”
Section: Neurocognitive Impairmentmentioning
confidence: 99%
“…Research has demonstrated that children with or without the characteristic facial features associated with PAE have similar patterns of CNS dysfunction (Mattson, Riley, Gramling, Delis, & Jones, 1998). The pattern of CNS dysfunction is somewhat variable by individual, but often involves impairments in complex information processing, learning and memory, executive functioning, social communication, and adaptive skills (Kodituwakku & Kodituwakku, 2014; Mattson, Crocker, & Nguyen, 2011). Additionally, children with FASD often display significant internalizing and externalizing behavior problems that interfere with their social relationships and functioning in home, school, and community settings.…”
Section: Introductionmentioning
confidence: 99%
“…The mean ages of FASD (M=11.14 years, SD=2.84; range 4 to 18) and non-FASD (M=10.97 years, SD=3.20; range 4 to 19) samples were both approximately 11 years, t (92)=−0.41, p=0.69. The mean IQ score across FASD samples was in the Low Average range (M=85.44, SD=15.85) compared to an Average-level mean IQ (M=103.11, SD=12.92) across non-FASD samples, t (56)=5.31, p<0.0001; these IQs are representative for the respective populations(Kodituwakku and Kodituwakku 2014; Mattson et al 2011 for reviews). A large portion of both samples (47 % for FASD and 57 % for non-FASD) were Caucasian.…”
mentioning
confidence: 97%
“…Prenatal exposure to alcohol in utero can result in a cluster of physical, behavioral, and neurocognitive abnormalities, called Fetal Alcohol Spectrum Disorders (FASD; Kodituwakku and Kodituwakku 2014;Mattson et al 2011 for a review). FASD has been estimated to occur in 2.4 -4.8 % of children (May et al 2009).…”
mentioning
confidence: 99%